QUALITY OF STUDENT ADMINISTRATION SERVICES - Joko Supriyanto; Sri Rejeki (Universitas Katolik Widya Karya Malang, 2023)
Institute of Business and Informatics STIKOM Surabaya is one of the private universities in Surabaya. STIKOM Surabaya has two faculties namely Faculty of Technology and Informatics, and Faculty of Economics and Business. Faculty of Technology and Informatics has several departments. They are S1 Information System, S1 Computer System, S1 Visual Communication Design, Graphic Design S1, Multimedia Computer DIV, and DIII Informatics Management, while Faculty of Economics and Business has three departments. They are: S1 Management Department, S1 Accounting Department, and DIII Computerized Office and Secretarial Department